SELF-EFFICACY SCALE VALIDATION AMONG FOOTBALL PLAYERS (ALGERIA) - mouloud kenioua; Nawal Krine (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The purpose of this study was to adapt the Algerian football players of general self-efficacy scale (GSES) developed by Schwarzer & Jerusalem (1995) which were adapted into more than thirty-three languages. The study conducted on a total of 216 male football players, ranging in age from 15-18 years. After translating the scale according to the local language, it was presented to specialists in psychology and sports psychology to formulate it to suit the applied category. the principal components analysis with varimax rotation was used for the construct validity.The results indicated that there are two-factor structure, the two factors together explained 54.5 % of the total variance. The reliability scales were found by Alpha Cronbach coefficient (0.79). These results confirmed that the self-efficacy scale among football players valid and reliable. It is necessary to conduct future studies in the local culture and on different sports and ages.